Fusion of duodeno-ileal omega switch and stomach pouch reconstruction as revisionary surgery for failed laparoscopic adjustable gastric banding and sleeved lesser curvature resection - Wojciech K. Karcz; Cheng Zhou; Piotr Małczak; Hryhoriy Lapschyn (Videosurgery and Other Miniinvasive Techniques)
Revisionary bariatric surgery procedures are becoming more frequent. Facing the challenge of complicated digestive tract changes after redo surgery, it is crucial to choose an appropriate method. Duodeno-ileal omega switch (DIOS), with growing clinical value as an easy malabsorptive procedure, has emerged as a treatment option. We would like to present a case of a 52-year-old obese male patient with a history of laparoscopic adjustable gastric banding and removal of a lesser curvature as a revision procedure to restore the restriction. In order to improve the patient’s health outcome, a two-stage re-revision procedure was performed, including DIOS to reduce the weight of the patient and a gastric pouch reconstruction in order to achieve a better satiety effect. This case study illustrates the intrinsic potential of malabsorption surgery and makes us believe that it may be used as the primary operation in two-staged procedures for revisionary surgical treatment.